ANALISIS AKAD ISTISHNA’ PADA KONVEKSI KOPPONTREN AUSATH BLOKAGUNG BANYUWANGI DALAM PRESPEKTIF HUKUM EKONOMI ISLAM - Hasyim Musyafa; Moh. Khozin Kharis (Jurnal Ekonomi Syariah Darussalam, 2025)
This study aims to determine the implementation of the istishna' contract in garment factories and to determine the solution to problems when there is a discrepancy in the ordered goods during the istishna' contract at the Koppontren Ausath Blokagung Tegalsari Banyuwangi garment factory. This research is a qualitative descriptive study, with data collected through observation, interviews, and documentation. After conducting in-depth research and interviews with informants, it can be concluded that the uniform ordering practice at the Koppontren Ausath Blokagung Banyuwangi garment factory meets the requirements and pillars of the istishna' contract, as evidenced by the author's observations of field conditions through interviews with the garment factory head, purchasing staff, and consumers. It can be concluded that the implementation of the istishna' contract is in accordance with Islamic economic law, and the resolution of the problem of discrepancies in the istishna' contract at the Koppontren Ausath garment factory is in accordance with Islamic law.